Eficiência fotossintética da cana-de-açúcar após a aplicação dos herbicidas s-metolachlor e atrazine em pós-emergência - Girotto, Marcelo [UNESP] (2010)
The objective of the work was to evaluate the photosynthetic efficiency through electrons transport rate in sugar cane crop, after S-metolachlor and atrazine herbicides application in post-emergence. For planting sugar cane cuttings (SP80-3280 genotype), vases with 8 dm3 capacity were used for atrazine and S-metolachlor application. Application was performed through a stationary sprayer installed in laboratory and after treatments application, plants were transported to a green house and kept until the end of the study. Reading of electrons transport rate (ETR) in the middle portion of sugar cane young leaves, with a portable fluorometer (Yield protocol) in intervals of 01, 04, 24, 48, 72 and 96 hours after application were conducted. Results demonstrated that SP80-3280 sugar cane genotype presented satisfactory selectivity to herbicides applied in post-emergence conditions, outstanding atrazine. Greatest reductions in ETR and phytointoxication were detected with S-metolachlor herbicide, with the use of fluorometer being considered an alternative and complementary methodology to evaluate herbicides selectivity.